The Effect of Utilitarian Values ​​on Increasing E-Wallet Application Users Repurchase Interest OVO for The Rinra Makassar Hotel Employees - Monica, Christin; Rizal S, Muh; Arhas, Sitti Hardianty (Jurnal Administrasi Bisnis, 2025)
The effect of utilitarian value on increasing the repurchase interest of application penggunas e-wallet OVO this to hotel employees The Rinra Makassar. Thesis. Business Administration Study Program. Administration Science Department. Faculty of Social Sciences and Law. Makassar public university. Supervised by Muh. Rizal and Sitti Hardiyanti Arhas. This study aims to determine how the influence of utilitarian values to the increase in repurchasing interest of hotel employees The Rinra Makassar. To achieve this goal, researchers use indicators to measure these variables. In utilitarian value variables with indicators cost, cost saving, convenience, affordability, multiple banefit. As for the variable interest in repurchasing with the indicators used, Repurchase, Revisit the application, Recommendation. In this study the research method used was quantitative method, with data collection techniques through questionnaires and documentation. The sample used was 75 respondents, resulting from the Slovin formula. The data were obtained from the results of the research and processed using data analysis and the help of the SPSS version 25 program which consisted of validity and reliability tests, simple linear regression analysis and the coefficient of determination. The results showed that the indicator used for each variable was the utility value (X) is in the good category and repurchase intention variable (Y) is in the good category. This shows that the utility value variable has a significant influence on the repurchase intention of application penggunas e -wallet this to hotel employees The Rinra Makassar. This is proven by the t test and the coefficient of determination test on the data obtained.